Management of Open Abdomen: Single Center Experience - Hakan Yanar; Emre Sivrikoz (Gastroenterology Research and Practice)
Aim. The authors reviewed their experience in the management of open abdomen using the vacuum-assisted closure (VAC), in order to assess its morbidity, and the outcome of abdominal wall integrity. Methods. A retrospective review was performed using the trauma registry to identify patients undergoing temporary abdominal closure (TAC) either using Bogota Bag (BB) or VAC, from January 2006 to December 2012. Inclusion criteria were TAC and survival to definitive abdominal closure. Data collected included age, indication for TAC, number of operating room procedures, primary fascial closure rate, and complications. Results. During the study period, 156 patients required one type of TAC. Mean number of operations required in BB group was 3.04 as compared to 1.96 in VAC group (). Survival was significantly increased in the VAC group (). The difference in primary closure rates did not reach statistical significance (25% vs. 55%; ). Complications were observed less frequently in the VAC group (). The mean time for fascial closure was 21 (±12) days in the BB group, as opposed to 6 (±3) days in the VAC group (). Conclusion. The vacuum assisted closure (VAC) has a significantly faster rate of closure, requires less number of operations, and is associated with a lower complication rate.